Results of Magnetic-Field Measurements with the 6-m Telescope. VI. Observations in 2012 - I. I. Romanyuk (2020)
© 2020, Pleiades Publishing, Ltd. Abstract—The paper presents complete results of measurements of the magnetic-field longitudinal component Be and radial velocities VR for 163 objects, mainly main-sequence chemically peculiar stars and standards. Observations were carried out in 2012 at the 6-m BTA telescope using the Main Stellar Spectrograph (MSS) equipped with a Zeeman analyzer. Six new chemically peculiar magnetic stars were discovered: HD84 882, HD109 030, HD170 054, HD189 775, HD341 037, and BD + 61°2436. The observations were carried out during 18 nights, 560 circularly-polarizedspectra were detected. New data were obtained for 120 magnetic stars (including 5 standard stars) and 43 non-magnetic stars (including nine standard stars). The radial velocities of all objects were measured; for 46 stars, they were obtained for the first time. Observations of standard magnetic and non-magnetic stars confirm the absence of any significant systematic errors capable of introducing distortions into the measurement results of Be. The paper provides comments on the research results for each of 163 stars.